Clinical application of Momordica charantia (Bitter Melon) for reducing blood sugar in type 2 diabetes mellitus - Ashley Dahlquist; Dana Jandali; Mirielle C. Nauman; Jeremy J. Johnson (International Journal of Nutrition, 2023)
Bitter melon is a popular fruit cultivated in Southeast Asia and other tropical climate regions. Bitter melon has been used in traditional medicine because of its numerous medicinal benefits, including having hypoglycemic effects. This has an indication for diabetic patients, and several clinical trials have provided evidence that orally administered bitter melon extract can reduce A1C and blood sugar levels in diabetes patients. In vitro and in vivo mechanistic studies suggest that bitter melon’s anti-diabetic actions work through intra- and extra-pancreatic mechanisms. Herein we summarize and highlight these mechanistic and clinical studies that have demonstrated the hypoglycemic effects of bitter melon in type 2 diabetes patients.
Keywords: Bitter melon